CARA MENGATASI MORNING SICKNESS PADA IBU HAMIL TRIMESTER I DI BPS NY. WAHYU SUROWATI DESA WARUNGDOWO POHJENTREK PASURUAN - Priyanti, Sari (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
The aim of this study was to identify the solution of morning sickness of pregnant woment in first trimester in BPS Ny Wahyu Surowati Karangdowo Pohjentrek Pasuruan. The research used descriptive design and first trimester pregnant woment used as population. The sample as much as 32 mothers. The result showed that there is 15 responden (68,3%) mothers try to handle morning sickness. Mothers knowing about pregnant and morning sickness influent what will they do if they have this sickness. So by reading KIA handbook and, hunting information from mass media like tv or radio about how to handling morning sickness would increase mothers knowledge that could be use in the second pregnant. Kata kunci: morning, sickness, pregnant.